Preparation, Characterization and Sensitive Gas Sensing of Conductive Core-sheath TiO2-PEDOT Nanocables - Yu Lei; Yu Ding; Timothy Strout; Wenzhao Jia; Ying Wang (Sensors, 2009)
Conductive core-sheath TiO2-PEDOT nanocables were prepared using electrospun TiO2 nanofibers as template, followed by vapor phase polymerization of EDOT. Various techniques were employed to characterize the sample. The results reveal that the TiO2 core has an average diameter of ~78 nm while the PEDOT sheath has a uniform thickness of ~6 nm. The as-prepared TiO2-PEDOT nanocables display a fast and reversible response to gaseous NO2 and NH3 with a limit of detection as low as 7 ppb and 675 ppb (S/N=3), respectively. This study provides a route for the synthesis of conductive nanostructures which show excellent performance for sensing applications.